Architectural modelmaking - Dunn, Nick, 1974- (London : Laurence King Pub., 2010)
The physical scale model is often cited as an important tool of communication for architecture students and practitioners alike. This book focuses on the inspiring possibilities for modelling the built environment with all the different media and techniques that are now available.
Includes bibliographical references and index.
Keywords: Architectural models; Architectural models -- Design and construction